RELIGIOSITY AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) IN SUPPORTING COMMUNITY ENGAGEMENT DURING THE COVID-19 PANDEMIC: WORK FROM HOME (WFH) AND WORK FROM OFFICE (WFO) - Octaffiani, Desprina; Violita, Evony Silvino (Journal of Environmental Science and Sustainable Development, 2022)
Pandemic COVID-19 that is currently faced by all countries has changed the wheels of workers' lives in all sectors. Keeping work performance in good quality is needed to in improving company performance. One way that is considered important to maintain the performance of the workforce is by voluntary social support received from co-workers or what is called Organizational Citizenship Behaviour (OCB). This study examines the correlation o of job satisfaction and religiosity on OCB behaviour. Because while religious belief and the level of religiosity are an important part of a person's life, many studies have been conducted to test this., However, due to but the circumstances of the COVID-19 pandemic which divided workers into WFH and WFO, this has allowed organizations to make different regulations for organizational productivity. With the purposive sampling technique, the total number of respondents is 416 workers who live in Bogor, Depok, Tangerang, and Bekasi (Jakarta and West Java). Data were analysed using PLS-SEM (Partial Least Square-Structural Equation Model) with the software Smart PLS. This study does not prove the direct influence of religiosity on OCB’s employees. In addition, in the pandemic situation, which requires most of the employees to work with the Work from Home (WFH) system, it does not show a significant effect on the relationship of religiosity to OCB behaviour, while Work from Office (WFO) workers are proven to show more helping behaviour that influenced by the level of their religiosity. This research is expected to be an illustration of how important it is for increasing job satisfaction that will make the workers more aware and willing to take action to help co-workers during the COVID-19 pandemic.